Trends in Consumer Behavior of Banking Products and Services - PETRESCU, Ramona (Journal of Advanced Research in Management; Vol 8 No 1 (2017): JARM Volume VIII Issue 1(15) Summer 2017, 2017)
Satisfaction of the need for products and services is achieved through consumption, preceded by a succession of actions by which the consumer decides to purchase a certain service, according to its requirements. An understanding individual need for financial-banking services not only helps developing and selling products and services, but is also a proof of the bank's concern with customers. Understanding consumer behavior helps a bank to anticipate the likely response of a customer and can influence the structure and planning the services offered by the banks.